Improving Students’ Reading Comprehension of Descriptive Text through Cognitive Strategy - Etfita, Fauzul (J-SHMIC : Journal of English for Academic, 2016)
This research aimed to explain the extent to which cognitive strategy can improve the students’ reading comprehension and what factors that influence the changes of the students’ reading ability by implementing cognitive strategy. This research was a classroom action research which consists of two cycles and four meetings of each cycle. Three meetings for teaching reading comprehension of descriptive text by using cognitive strategy and another meeting for reading comprehension of descriptive text test. The research was conducted from April, 30 2013 up to May, 30 2013. The instrument used to collect the data were reading comprehension of descriptive text test, observation sheets, field notes, and interview which were helped by a collaborator. The finding revealed that the implementation of cognitive strategy could better improve students’ reading comprehension of descriptive text at grade VII-2 of SMPN 1 Indra Praja Tembilahan. The improvement was confirmed by the increasing average students’ score, the average score of students in cycle I was 70,72 and in cycle II was 78,10. The factors that influence the students’ reading comprehension during the application of cognitive strategy were the materials, the students’ reading  motivation, and the teacher’s role to students. Finally, the classroom action research by using cognitive strategy could improve the students’ reading comprehension of descriptive text at grade VII-2 SMPN 1 Indra Praja Tembilahan.